Reward for environmental performance: using the Scanlon Plan as catalyst to green organisations. (29th December 2008) - Massoud, Jacob A.; Daily, Bonnie F.; Bishop, James W.
Institutionalising, a reward system based on measurable performance and incentives for environmental improvements, serves as a potential mechanism to enhance a firm's environmental performance. Our main purpose is to integrate the principles of environmental management and the Scanlon Plan as a means to achieve this. Specifically, our paper advocates the utilisation of Scanlon Plan principles for environmental performance. The Scanlon Plan features (1) collectiveness and cooperation, (2) employee participation, (3) quantifiable performance and bonus measures and (4) an equitable reward system; all components that would enhance environmental performance.